Elderly sexual abuse: theory, research, and practice - Beauregard, Eric (Routledge studies in crime and society, 2022)
"This book offers an analytical review of the state of knowledge on elderly sexual abuse and presents new data that will confront some of the accepted ideas and some of the myths associated with this specific form of sexual violence. Sexual violence research has often considered children to be the most vulnerable population. However, another population just as vulnerable to sexual abuse but often overlooked by researchers, is the elderly. Evidence shows that elderly victims are more likely to be attacked by strangers, most likely to be victimized in their own homes and are usually less capable of resisting a physical attack. Drawing on a large and representative data-set, Elderly Sexual Abuse offers a full and theoretically informed picture of the offenders and their crimes. In addition to a specific chapter devoted to prevention and criminal investigation, the book also connects research to practice, exploring what the findings mean for professionals working with these cases and the criminal justice system. This book is essential reading for all those engaged with sexual violence, victimization, elder abuse and vulnerable populations"--